A Living Hadith Analysis of Thalab al-‘Ilm in Shaping Students’ Learning Ethos in Indonesian Islamic Schools - M. Affan Ramadhan; Sedya Santosa; Hajir Ahmad; Muhammad Buya Al-Madany Abror (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2026)
This study addresses the limited analytical use of the Living Hadith framework in Islamic education research, which often remains descriptive and underexplores how hadith values are internalized and embodied in students’ learning behavior. This research aims to examine how the hadith ṭalabul ‘ilmi farīḍah ‘alā kulli muslim is transmitted, interpreted, internalized, and embodied within a school context. Using a qualitative case study combined with a phenomenological approach, data were collected through participatory observation, in-depth interviews, and documentation at SMA X Yogyakarta. The analysis is structured using four dimensions of Living Hadith: transmission, interpretation, internalization, and embodiment. The findings reveal three patterns of interpretation (normative-textual, functional-practical, and integrative-contextual), two forms of internalization (intrinsic motivation and affective commitment), and an “embodiment gap” where students’ religious awareness is not consistently reflected in academic behavior. The study contributes theoretically by operationalizing Living Hadith as an analytical framework linking text, meaning, and practice, and practically by highlighting the need for integrative pedagogical strategies that bridge spiritual values and everyday learning habits. These results suggest that embedding hadith values in education requires not only repeated transmission but also reflective engagement and contextual adaptation to students’ social and digital realities. ABSTRAK Penelitian ini berangkat dari keterbatasan penggunaan kerangka Living Hadith dalam studi pendidikan Islam yang masih cenderung bersifat deskriptif dan belum mengkaji secara mendalam bagaimana nilai-nilai hadis diinternalisasi dan diwujudkan dalam perilaku belajar siswa. Penelitian ini bertujuan untuk menganalisis bagaimana hadith ṭalabul ‘ilmi farīḍah ‘alā kulli muslim ditransmisikan, diinterpretasikan, diinternalisasi, dan diwujudkan dalam konteks sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus yang dipadukan dengan pendekatan fenomenologis. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi di SMA X Yogyakarta. Analisis dilakukan menggunakan empat dimensi Living Hadith: transmisi, interpretasi, internalisasi, dan embodiment. Hasil penelitian menunjukkan tiga pola interpretasi (normatif-tekstual, fungsional-praktis, dan integratif-kontekstual), dua bentuk internalisasi (motivasi intrinsik dan komitmen afektif), serta adanya “kesenjangan embodiment” di mana kesadaran religius siswa belum sepenuhnya tercermin dalam perilaku akademik sehari-hari. Secara teoretis, penelitian ini berkontribusi dengan mengoperasionalkan Living Hadith sebagai kerangka analitis yang menghubungkan teks, makna, dan praktik. Secara praktis, penelitian ini menekankan pentingnya strategi pedagogis integratif yang mampu menjembatani nilai spiritual dengan kebiasaan belajar siswa. Temuan ini menunjukkan bahwa integrasi nilai hadis dalam pendidikan tidak cukup melalui transmisi yang berulang, tetapi memerlukan keterlibatan reflektif dan adaptasi kontekstual terhadap realitas sosial dan digital siswa.